Evaluation of Patients with Tall Stature Applying to a Pediatric Endocrinology Clinic - Aşan Önder Çamaş; Inara Eldarova; Burçin Çiçek; Sibel Ergin Şahin; Merve Nur Hepokur (Galenos Yayinevi, 2024)
Aim: Tall stature, defined as a height greater than 2 standard deviation score (SDS), affects 2.3% of children. Our study aimed to explore the causes of tall stature in children and assess the long-term outcomes for these cases. Materials and Methods: This study included 393 children with tall stature who applied to a pediatric endocrinology clinic between 2015-2024. The patients' medical histories, physical examinations, laboratory findings and hormonal profiles were recorded. Results: Two hundred and forty-seven girls (62.8%) and 146 boys (37.2%) with a mean age of 9.0±2.8 (0.7-16.8) years were included. The majority of the cases presented with obesity and tall stature (25.2%), early onset of puberty signs and tall stature (18.8%), and early onset of puberty signs (12%). Tall stature was not reported as a complaint in 32.7% of the patients. At the initial visit, the height SDS was 2.6±0.5 (2.0-6.2), the mid parenteral height (MPH) SDS was 0.1±0.8 [(-1.9)-3.6] and the predicted adult height (PAH)-MPH was 8.5±7.8 [(-8.5)-39.0] cm. Considering their diagnoses, the majority were familial tall stature (39.9%), obesity + tall stature (32.3%), and central precocious puberty (13.5%). Cranial imaging was performed in 33 cases, and pathology was detected in 10. 95 of the cases had reached their final height. There was a statistically significant difference between the final height SDS and the patients' initial height SDS and MPH SDS values (p<0.001). There was no difference between their PAH and final height values (p=0.481). Conclusion: Those individuals with tall stature required fewer hospital admissions than those with short stature. Obesity, precocious puberty, and genetic potential were found to be the most significant triggering factors, so they should not be overlooked.